LITERATURE REVIEW: CHARACTER VALUE DEVELOPMENT THROUGH CHEMISTRY LEARNING - Noviza Rizkia; Azzahrah, Suci; Nisa Kanahaya Br Tarigan (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2025)
Chemistry learning is not only focused on mastering concepts and cognitive skills, but also holds significant potential in shaping and developing students' character values. This literature review aims to analyze various approaches and strategies in chemistry   education   that   integrate   character   values   such   as   responsibility, collaboration,  honesty,  and  environmental  awareness.  The  findings  indicate  that contextual  approaches,  project-based  learning,  and  the  integration  of  values  in laboratory experiments are effective methods for instilling character values. Therefore, chemistry teachers need to design learning that is not only oriented toward academic outcomes but also toward character development as part of holistic education.